Surgical treatment of traumatic cervical facet dislocation: anterior, posterior or combined approaches? - Catarina C. Lins; Diego T. Prado; Andrei F. Joaquim (Arquivos de Neuro-Psiquiatria)
ABSTRACT Surgical treatment is well accepted for patients with traumatic cervical facet joint dislocations (CFD), but there is uncertainty over which approach is better: anterior, posterior or combined. We performed a systematic literature review to evaluate the indications for anterior and posterior approaches in the management of CFD. Anterior approaches can restore cervical lordosis, and cause less postoperative pain and less wound problems. Posterior approaches are useful for direct reduction of locked facet joints and provide stronger fixation from a biomechanical point of view. Combined approaches can be used in more complex cases. Although both anterior and posterior approaches can be used interchangeably, there are some patients who may benefit from one of them over the other, as discussed in this review. Surgeons who treat cervical spine trauma should be able to perform both procedures as well as combined approaches to adequately manage CFD and improve patients’ final outcomes.